Symmetric and asymmetric modeling of entrepreneurial ecosystem in developing entrepreneurial intentions among female university students in Saudi Arabia. Issue 4 (7th November 2019) - Ali, Imran; Ali, Murad; Badghish, Saeed
Abstract : Purpose: Unlike previous studies that examine the role of different entrepreneurial ecosystem factors in predicting entrepreneurial intentions. The purpose of this study is to explain the direct effects of entrepreneurial ecosystem factors effecting entrepreneurial intentions and configurational combinations of entrepreneurial ecosystem factors that cause high or low entrepreneurial intentions among female university students in Saudi Arabia. Design/methodology/approach: The study used structured survey-questionnaire based data collected from 310 female students enrolled in different universities in Saudi Arabia. The study used symmetric analysis using structural equation modeling technique, whereas asymmetric analysis is performed using the fuzzy-set qualitative comparative analysis, necessary condition analysis is also used to identify the role of different entrepreneurial ecosystem factors in increasing and/or decreasing entrepreneurial intentions among young Saudi women. Findings: The results of symmetrical analysis show that access to finance, access to physical infrastructure, and cultural factors are not significantly associated with entrepreneurial intentions, whereas government policies and regulations, government programs and support, social factors and entrepreneurship education and training are significantly associated with the development of entrepreneurial intentions among female Saudi university students. While the result of asymmetrical analysis provides 15 configurational models that explains the high levels of certain factors to predict entrepreneurial intentions among female university students in Saudi Arabia. Specifically, social support is found as necessary condition in majority of models to predict high levels of entrepreneurial intentions among female Saudi university students. Practical implications: The results of the study provide empirical evidence to policymakers in Saudi Arabia. The study proposes that it is not mandatory that the high levels of all entrepreneurial ecosystem factors are important to predict high entrepreneurial intentions, rather in some conditions the low levels of certain factors are obligatory to predict high levels of entrepreneurial intentions. Originality/value: Two-step mix-method approach is used in this study containing analysis of symmetric within entrepreneurial ecosystem increase or decrease entrepreneurial intentions among female university students in Saudi Arabia. There has been plenty of research that examines the role of entrepreneurial ecosystem factors in development of university students' entrepreneurial intentions, however there is less research evident in the entrepreneurship literature that examine the configurational effects of factors within entrepreneurial ecosystem in increasing and/or decreasing entrepreneurial intentions among female university students.